2018
DOI: 10.1101/395145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Independent component analysis provides clinically relevant insights into the biology of melanoma patients

Abstract: The integration of publicly available and new patient-derived transcriptomic datasets is not straightforward and requires specialized approaches to deal with heterogeneity at technical and biological levels. Here we present a methodology that can overcome technical biases, predict clinically relevant outcomes and identify tumour-related biological processes in patients using previously collected large reference datasets. The approach is based on independent component analysis (ICA) -an unsupervised method of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Furthermore, in several studies it was found that stabilized or consensus independent components have better characteristics in terms of generalization and interpretation [34,38,39,40,41]. By stabilization one usually means re-computing ICA using multiple random initialization with subsequent clustering of the resulting components [40,41].…”
Section: Methodology Of Ica Application To Cancer Omics Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in several studies it was found that stabilized or consensus independent components have better characteristics in terms of generalization and interpretation [34,38,39,40,41]. By stabilization one usually means re-computing ICA using multiple random initialization with subsequent clustering of the resulting components [40,41].…”
Section: Methodology Of Ica Application To Cancer Omics Datamentioning
confidence: 99%
“…Another component frequently identified in the analysis of transcriptomic data is related to GC-content, which might reflect the influence of GC-content on the RNA amplification step common for both microarray-based and sequencing-based methodologies. In Reference [39], a small dataset of three primary melanoma tumors and two matched controls, characterized at the level of transcriptome and miRNA, were merged together with a large reference melanoma dataset from the Cancer Genome Atlas. The ICA decomposition was performed for the merged transcriptomic and miRNA data separately.…”
Section: Applications Of Ica In Cancer Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…ICA is a technique for unsupervised exploration of multichannel data widely used in many areas of science. The use of ICA can be found, for example, in biology and medicine [63][64][65][66][67], chemistry [68][69][70], astronomy [71,72], financial analysis [73,74], marketing [75], engineering [76], etc. ICA is also often used to preprocess data obtained from EEG [77][78][79][80].…”
Section: Data Pre-processingmentioning
confidence: 99%
“…Tasks of this kind are solved using data mining algorithms such as data dimensionality reduction and cluster analysis [10,13,14]. Dimensionality reduction algorithms allow switching to a low-dimensional space without losing the essence of information [15,16]. Cluster analysis algorithms make it possible to determine clusters of data specifi ed in varying degrees of similarity, the number of which may be associated with aggregates of molecular compounds.…”
mentioning
confidence: 99%